Factors Associated with Research and Productivity among Faculty of Higher Education Institutions: Input to Enhancing Research Culture - Camilon, Maria Daisy F.; Callo, Eden C.; Panoy, Julie Fe D. (International Journal of Multidisciplinary: Applied Business and Education Research, 2024)
The role of research in an academic institution is significant for its sustainability and development, and it is imperative to have knowledge-driven growth based on innovation. The main objec-tive of this dissertation was to find out the factors associated with research and productivity among faculty of higher education insti-tutions in the LSPU System as input to enhancing research culture. Descriptive correlational research method was used to determine the factors associated with research and productivity among high-er education faculty institutions consisting of 232 regular faculty members among four campuses of Laguna State Polytechnic Uni-versity- San Pablo City Campus, Sta. Cruz Campus, Siniloan Campus and Los Banos Campus. The perceived level of self-motivation of the respondents on knowledge and skills, ability and interest, mo-tivation and drive is “very high”; the perceived level of institution-al support system for research among faculty of Laguna State Poly-technic University System on policies and guidelines, promotion and incentives, research program, budgeting, and external sourc-ing/funding is “highly evident”; perceived level of research- work-ing environment, is “very highly evident”; perceived level of re-search productivity for research reveals that the research produc-tivity is “very high”. Faculty’s research productivity is significantly predicted by self-motivation, an institutional support system for research; and the research working environment; teacher’s per-ceived self-motivation mediated with the institutional support system and the faculty’s research productivity; teacher’s perceived self-motivation mediated with the research working environment and to the faculty’s research productivity. ANOVA result revealed that there is no significant difference in the perceptions of the LSPU respondents on self-motivation, an institutional support sys-tem for research, research working environment, and research productivity when grouped according to their University Campus. In terms of the above findings, this study concluded the hypothe-ses stating that the research productivity of the faculty is not sig-nificantly predicted by self-motivation, an institutional support system for research, and the research working environment is not sustained. The faculty self-motivation does not mediate the effect of the institutional support system and research working envi-ronment on their research productivity is not sustained. There is no significant difference in the perceptions of the LSPU respond-ents on self-motivation, an institutional support system for re-search, research working environment, and research productivity.